FETAL DEVELOPMENT: STAGES, FACTORS INFLUENCING GROWTH, AND CLINICAL SIGNIFICANCE (Modern education and development, 2025)
Fetal development is a complex and finely regulated biological process that begins with conception and continues until birth. This article reviews the major stages of fetal development, examines critical internal and external factors that influence intrauterine growth, and discusses common complications that can arise during pregnancy. Understanding these aspects is essential for improving maternal and fetal health outcomes.